The Teachers Conception of Mathematical Modelling at Palembang - Cecil Hiltrimartin; Yusuf Hartono; Scristia Scristia (Pancaran Pendidikan, 2018)
This studyaimed  to analyze mathematicsteachersconceptions(beliefs) about mathematical modeling in Palembang. In this study presents a case study of 60 mathematics teachers, investigating their conceptions about mathematical modeling and their experiences of working with modeling activities in Palembang. In particular, basic concepts of mathematical models, mathematical modeling, and mathematical modeling in education were analyzed. Quantitative data were collected through a questionnaire of sample of practicing teachers of mathematics in Palembang. The data showed that mathematics teachers in Palembang hold several misconceptions about models and modeling, particularly regarding aspects of the mathematical modeling process. Specifically, the majority of teachers does not understand that the mathematical modeling process always requires making choices and assumptions, and that mathematical modeling situations must come from real-world scenarios. The results indicate that the teachers in this study seem not to give priority to integrating mathematical modeling into their everyday mathematics teaching.